Changes on quantitative traits of black gram (Vigna mungo (L.) Hepper) induced by EMS in M2 generation - L. Mullainathan, D. Arulbalachandran (Journal of Phytology, 2009)
The systematic collection of black gram is displayed inadequate variability for biotic and abiotic desirable genes. It is possible that genes for high productivity could have been lost due to overriding role of natural selection and genetic base of the present day collection remains poor due to lack of genetic variability owing to their autogamous nature. Mutagenesis has been widely used as a potent method of enhancing variability for crop improvement. In the present investigation, the genetic variability was induced to improve quantitative traits of black gram in M2 generation induced by EMS. The results showed that a significant enhancement in quantitative mean performance archived at 0.1% EMS concentration.Ã‚Â